Gatherings in Pharmacie’s Back Rooms in Borobo’s Plays. Aura’s Case and Polycrate’s Complex - Acuña, Ana (Madrygal. Revista de Estudios Gallegos, 2004)
In this paper we intend to deal with Borobo’s unpublished plays. We will start from Borobo’s personal interviews, his works, other than theatre (essays, poetry, cinema scripts), and his articles in the newspaper La Noche. Then, we will deal with the third act of Aura and the Polycrates Complex, the last of Borobo’s plays. The act analysed is relevant in terms of its treatment of space and characters. It is our aim to get an insight into the inner story, the reality underlying fiction. Theatre, reality-fiction, Madrid.